Constrictive labor and the dignity of work - Alessandro Roncaglia (PSL Quarterly Review, 2021)
The paper summarizes the rationale and contents of a conference held at the Accademia Nazionale dei Lincei in December 2020, celebrating the fiftieth anniversary of the Italian Statuto dei lavoratori (Charter of Workers' Rights): a reform that represents an important advancement in Italian civic development. The paper illustrates the Charter: its attempt to reconcile, in light of the Italian Constitution, the twin and opposite characteristics of labor as sacrifice and as contributing to the social dignity of workers; and the law's compromises between the opposite needs of the labor process (stability and flexibility of employment, employers' freedom in hiring, the need to avoid discrimination, and so on).
Keywords: J08; J28; J48; J53; J83; 330; Charter of Workers' Rights; industrial relations; labor reforms